2016
DOI: 10.3389/fmats.2016.00036
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to the Description of Constitutive Relations

Abstract: Recent advances in the development of implicit constitutive relations to describe the response of both solids and fluids have greatly increased the repertoire of the modeler in his ability to describe natural phenomena more faithfully than hitherto possible. It would not be an exaggeration to claim that such constitutive relations have the potential to lead to breakthroughs in mechanics as they provide very promising novel means to study two of the most important and ill-understood problems in mechanics, that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 59 publications
(61 reference statements)
0
13
0
Order By: Relevance
“…where H denotes the Heaviside step function (5) and T y is a constant. This formula is motivated by the one-dimensional model (4).…”
Section: Thermodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…where H denotes the Heaviside step function (5) and T y is a constant. This formula is motivated by the one-dimensional model (4).…”
Section: Thermodynamicsmentioning
confidence: 99%
“…For example [3] and [4] have shown that the novel constitutive framework (2) can be gainfully exploited in the modelling of the response of rubber. (See [5] and [6] for recent reviews of the applications of this concept in the mechanics of solids. )…”
Section: Introductionmentioning
confidence: 99%
“…As the first constitutive model, we generalize the basic second-grade fluid model proposed in Mctigue and others (1985), assuming that the characteristic constitutive parameters depend on the pressure p , the mean normal stress (Rajagopal and others (2012, 2015); Rajagopal (2015); Rajagopal and Saccomandi (2016)): We thus consider 2 where tr( T + p I ) = 0. As stated earlier, we assume that the coefficients characterizing the constitutive Eqn (6) of the fluid may depend on p so that the constitutive model is implicit.…”
Section: The Modelmentioning
confidence: 99%
“…A generalization of Cauchy and Green elasticity has been initiated by Rajagopal and his co-authors in a series of papers [14][15][16][17][18][19][20][21][22], in which the authors describe the implicit constitutive models that have a strong tenor of thermodynamic framework. The response of an elastic body 1 is best described by the implicit constitutive relations between Cauchy stress and deformation gradient tensors [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%